La formación del educador especial desde la práctica pedagógica en tiempos de pandemia - Giraldo-González, Angie Katherine; Parra-Pretel, Angie Carolina; Florido-Parra, Geidi Giomara; Orozco-Herrera, María Daniela; Prada-Gómez, Néstor Camilo; Sánchez-Fonseca, Tania Isabel; Murcia P., María del Pilar (Lee La LEE, 2023)
La formación del educador especial desde la práctica pedagógica en tiempos de pandemia